(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Although applying industrialization methods on the construction industry is well-documented as one of the best solutions of high housing demands, implementation progress of industrialized building system (IBS) rather slow is picking up due to barriers associated with complexity of its design stage. The paper presents an extant literature survey focusing on application of modular design process on IBS projects to benefit from abstraction of design process of these projects in order to facilitate the industrialization process of the construction industry. Results indicate that designing based on modularization could assist design process of IBS projects so that it prevents emerging conflicts in IBS life span that is rooted in IBS design stage. The study is presently expecting to improve awareness in various phases of IBS projects regarding the significance contributions of Modular Design Method as a respond to the complexity of IBS design method.